Menjawab Kebekuan Fikih Indonesia dengan Filsafat Hukum Islam - Ihyak Ihyak (AN NUR: Jurnal Studi Islam, 2021)
Jurisprudence needs flavoured Indonesia is increasingly rising. This is due to the emergence of a wide range of contemporary problems faced by Muslims in Indonesia. Classical Fikih produced by scholars’ classical era felt no longer able to stem the rapid flow of modernization. To produce a product of jurisprudence that can ensure justice for human benefit and Indonesia as well as contextual, it takes a variety of approaches in the method of taking the law (ijtihad). Ijtihad now can not just use one approach but must be multi-disciplinary due to the complexity of problems faced by humans contemporary y. Ijtihad is done by the scholars’ have to integrate a wide variety of methods and cross-scientific. In this way, the legal substance will be taken muamalah beneficial to human civilization and Indonesia. One approach that is forgotten by the mujtahid in Indonesia is the philosophical approach. Though this approach is very important to be able to catch the substance or the spirit of the text so as to ensure the welfare and human justice everywhere and forever. This article will break down how important the philosophy of Islamic law is in solving various problems faced by the community, the nation and the State